Below the surface: The inner lives of TLR4 and TLR9. Issue 1 (22nd March 2019) - Marongiu, Laura; Gornati, Laura; Artuso, Irene; Zanoni, Ivan; Granucci, Francesca
Abstract: TLRs are a class of pattern recognition receptors (PRRs) that detect invading microbes by recognizing pathogen-associated molecular patterns (PAMPs). Upon PAMP engagement, TLRs activate a signaling cascade that leads to the production of inflammatory mediators. The localization of TLRs, either on the plasma membrane or in the endolysosomal compartment, has been considered to be a fundamental aspect to determine to which ligands the receptors bind, and which transduction pathways are induced. However, new observations have challenged this view by identifying complex trafficking events that occur upon TLR-ligand binding. These findings have highlighted the central role that endocytosis and receptor trafficking play in the regulation of the innate immune response. Here, we review the TLR4 and TLR9 transduction pathways and the importance of their different subcellular localization during the inflammatory response. Finally, we discuss the implications of TLR9 subcellular localization in autoimmunity. Graphical Abstract: Review on the importance of TLR4 and TLR9 dynamic subcellular localization in the inflammatory responses.